Les lieux de la répression au prisme du genre : la rue parisienne au croisement des pratiques émeutières et des pratiques policières (XVIIIe siècle) - Clara Chevalier (Genre & Histoire)
What spatial logics are at stake during the repression of Parisian popular uprisings in the XVIIIth century? The analysis of urban space during this period allows one to grasp the relationship between popular social practices and the police apparatus. The social divisions of urban space were not strict; moreover, it appears that popular social practices were not regulated by the sexual division of spaces. Significantly, the policing of the capital involved its division into police quarters. Through an investigation of the police archives concerning the repression of two riots, that took place on two different spatial scales, I will highlight how the police sought in particular to control the city’s boundaries. Because the discourses produced deal more specifically with the repression than with the actual riots, these documents shed light as well on the erasure of female rioters, emphasizing a sexual division of repression.